2021
DOI: 10.3390/cells10113056
|View full text |Cite
|
Sign up to set email alerts
|

The Increasing Role of Kappa Free Light Chains in the Diagnosis of Multiple Sclerosis

Abstract: Free light chains (FLC) are a promising biomarker to detect intrathecal inflammation in patients with inflammatory central nervous system (CNS) diseases, including multiple sclerosis (MS). The diagnostic use of this biomarker, in particular the kappa isoform of FLC (“KFLC”), has been investigated for more than 40 years. Based on an extensive literature review, we found that an agreement on the correct method for evaluating KFLC concentrations has not yet been reached. KFLC indices with varying cut-off values a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 134 publications
(630 reference statements)
1
19
0
2
Order By: Relevance
“…Specificity was 100% because only patients with an IND were above the threshold for positive k-FLC. Similar sensitivity and specificity have been reported in past studies of patients with more than one band in IEF, where k-FLC were measured quantitatively [ 9 , 19 ]. In this regard, our results are also mainly consistent with the ones of a previous study on only one isolated band [ 14 ].…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Specificity was 100% because only patients with an IND were above the threshold for positive k-FLC. Similar sensitivity and specificity have been reported in past studies of patients with more than one band in IEF, where k-FLC were measured quantitatively [ 9 , 19 ]. In this regard, our results are also mainly consistent with the ones of a previous study on only one isolated band [ 14 ].…”
Section: Discussionsupporting
confidence: 82%
“…The evaluation of k-FLC in laboratory work-up has proven to be a useful additional parameter within the diagnosis of intrathecal immunoglobulin synthesis [ 8 , 9 , 10 , 11 , 12 ], which has also been determined to be robust against external influences such as storage, plasma exchange and common therapy in acute exacerbation in MS (depending on drug concentration) [ 9 ]. Furthermore, in the case of artificial blood contamination of the CSF, k-FLC does not increase artificially compared with the Ig indices [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All FLCk negative samples revealed pathological OCB results in the silver staining method after isoelectric focusing on polyacrylamide gels. Studies using silver staining to detect OCB showed a better performance with higher rates of OCB-positive patients than other methods of OCB determination, even if the cause of this has not been conclusively clarified [ 30 ]. Therefore, we recommend that the OCB detection is performed by silver staining if a clinical suspicion of MS and negative FLCk levels are present.…”
Section: Discussionmentioning
confidence: 99%